2011
DOI: 10.1186/1748-717x-6-157
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral doses in patients undergoing Cyberknife treatment for intracranial lesions. A single centre experience

Abstract: BackgroundStereotactic radiosurgery/radiotherapy procedures are known to deliver a very high dose per fraction, and thus, the corresponding peripheral dose could be a limiting factor for the long term surviving patients. The aim of this clinical study was to measure the peripheral dose delivered to patients undergoing intracranial Cyberknife treatment, using the MOSFET dosimeters. The influence of the supplemental shielding, the number of monitor units and the collimator size to the peripheral dose were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Studies examining outcomes in this technology are a minority in comparison with those investigating SRS delivered by non-CK linear accelerators and Gamma Knife (GK; Elekta, Stockholm, Sweden). 24 27 Tamari et al analyzed a sample of 109 lesions treated with CK and demonstrated both lesion control at 1 and 2 years (83.3% and 78.5%, respectively) and rates of radionecrosis (7%) comparable to studies using GK and non-CK linear accelerator–based SRS. 27 Tumor volume ( P = .020) and prescription dose ( P = .023) were associated with LC.…”
Section: Discussionmentioning
confidence: 92%
“…Studies examining outcomes in this technology are a minority in comparison with those investigating SRS delivered by non-CK linear accelerators and Gamma Knife (GK; Elekta, Stockholm, Sweden). 24 27 Tamari et al analyzed a sample of 109 lesions treated with CK and demonstrated both lesion control at 1 and 2 years (83.3% and 78.5%, respectively) and rates of radionecrosis (7%) comparable to studies using GK and non-CK linear accelerator–based SRS. 27 Tumor volume ( P = .020) and prescription dose ( P = .023) were associated with LC.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a mouth bite positioned against the upper dentition attached to the stereotactic frame was applied to prevent any head tilt movement. The characteristics of the system have been previously described [ 16 ]. Before the CT localization a localizer box was mounted to the BrainLAB mask system in order to provide a three-dimensional (3D) stereotactic coordinate array for target localization.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately before treatment, all patients underwent CT verification to check the accuracy of isocenter position [ 16 ]. Firstly, the CT verification set was imported in the planning system and localized automatically by the planning software through identification of the stereotactic fiducials in the same way as for planning CT.…”
Section: Methodsmentioning
confidence: 99%
“…This is likely because all platforms typically treat similar volume targets. Furthermore, Vlachopoulou noted that the effect of collimator size on extracranial dose is limited to areas less than 29 cm from the target, which suggests that target volume (which increases inpatient scatter) may only affect the dose to the head, neck and upper thorax [29]. Although our data does not establish a functional dependence between prescription dose and extracranial dose, the prescription dose is a convenient descriptor facilitating comparison between different SRS treatment platforms, though we acknowledge that this can vary significantly depending on the target volume, shape, isocentre configuration and beam-on time.…”
Section: Discussionmentioning
confidence: 99%